Decay rates of solutions to Euler equations with time-dependent damping. (August 2020) - Zhang, Lina
Abstract: In this paper, we are concerned with the isentropic Euler equations with time-dependent damping like − μ 1 + t ρ u for physical parameter μ > 0 . By using the technical time-weighted energy method, the global existence is proved and the decay estimates are obtained for the solutions of Euler equations. It is interesting that the new decay estimates are dependent on the physical parameter μ . And the decay rates are much better than that obtained by Pan.